Development of a Detailed Log Booklet for social Ecological Physical Activity Research - Andrew T. Kaczynski (SAGE Publishing, 2012)
To advance social ecological research, tools are required to better assess the contextual nature of physical activity outcomes. This study describes the development of a detailed log booklet to capture relevant episode-specific data, including location and purpose, about participants' free-living activity patterns. The log was developed using definitions and questions from existing physical activity questionnaires as well as measures designed to elicit more specific and detailed information relevant to social ecological studies of physical activity. Utility of the log was tested with 580 community residents over seven days. It was found to be practical and feasible for use in community-based physical activity research, and yielded a wealth of episodic information about intensity, duration, location, purpose, and co-participants, among other details.